Clustering Wilayah Kerawanan Stunting Menggunakan Metode Fuzzy Subtractive Clustering - Ratna Dwi Christyanti; Dady Sulaiman; Adymas Putro Utomo; Muhammad Ayyub (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
Stunting is a chronic lack of nutrition experienced by toddlers, causing the body to be too short for its age. In Bulungan Regency, stunting is a problem that the government focuses on handling. Based on these problems, this study aims to determine the clusters of stunting susceptibility levels. The method used is Fuzzy Subtractive Clustering (FSC). The method stages in this research are data collection; clustering process using the FSC method; the process of determining the candidate cluster center; the cluster center consideration process using various parameters; then clustering the previously given data into the appropriate cluster based on the degree of membership of each. From this study it can be concluded that the radius (r) of 0.92 produces the best number of clusters. The number of clusters formed is 7 clusters as follows, cluster 1 has 2 sub-districts, cluster 2 has 3 sub-districts, cluster 3 has 3 sub-districts, cluster 4 has 1 sub-district, cluster 5 has 1 sub-district, cluster 6 has 1 sub-district, and cluster 7 has 1 district. Keywords: Stunting; Clustering ; Fuzzy Subtractive Clustering (FSC)